If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = -3(1 + 5x) + -3(3x + 1) 42 = (1 * -3 + 5x * -3) + -3(3x + 1) 42 = (-3 + -15x) + -3(3x + 1) Reorder the terms: 42 = -3 + -15x + -3(1 + 3x) 42 = -3 + -15x + (1 * -3 + 3x * -3) 42 = -3 + -15x + (-3 + -9x) Reorder the terms: 42 = -3 + -3 + -15x + -9x Combine like terms: -3 + -3 = -6 42 = -6 + -15x + -9x Combine like terms: -15x + -9x = -24x 42 = -6 + -24x Solving 42 = -6 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. 42 + 24x = -6 + -24x + 24x Combine like terms: -24x + 24x = 0 42 + 24x = -6 + 0 42 + 24x = -6 Add '-42' to each side of the equation. 42 + -42 + 24x = -6 + -42 Combine like terms: 42 + -42 = 0 0 + 24x = -6 + -42 24x = -6 + -42 Combine like terms: -6 + -42 = -48 24x = -48 Divide each side by '24'. x = -2 Simplifying x = -2
| 22*16= | | 1.3=5980000000000000000000000000/x | | 5x+15(22+9x)=50 | | (x-2)*180=3240 | | 2sin^2x=-sinx | | 1-cos(t)=1.5 | | 1-cos(2t)=1.5 | | 3(4x+5)+2(x-7)+6x= | | 16x^5=81x | | x^6+8x^3+16=0 | | y-6=-3(x-4) | | f(t)=-5t+20t+60 | | 5(-7)-2(-3)= | | -30a-5a= | | -5=-11u | | 3x^2+5xy+y^2-4=0 | | x+9+x= | | Log(x)=3.4 | | 8-6(1-9f)=-30 | | ab=5-5c | | 4r^4-8r^2+16= | | 0.3(3x-12)+11=1+1.5x | | 7x-12=15+4x | | 4r^4-8r^2=16 | | 8x+5=13x-6 | | x(6+10)=58 | | 540-14p=120 | | -2+8+x+(-12)=(-17)+9 | | 6x+11x-25+13x-35+6x+35+8x+15+9x-5+7x+15=900 | | 10x-4+4+4+x-22=0 | | 8-(-3-7x)-2(5x+3)=36 | | n^2+2n-19=5 |